Gem-Grade Garnet With Metamorphic Origin in the Tiemurt Orogenic-Type Deposit, Chinese Altay Orogen: Texture, Chemistry, and Physicochemical Condition - Hu, Zhaobin; Zheng, Yi; Yu, Pengpeng; Wu, Yihan; Wang, Chengming (Frontiers in Earth Science, 2021)
Reddish gem-grade garnet grains are widespread in the Au-Cu-Pb-Zn sulfide deposits of Chinese Altay Orogen, and how their formation links to seafloor sedimentation, magmatic hydrothermal metasomatic, or orogenic metamorphism remains unclear. In this context, we present an integrated set of geological occurrences, mineral internal texture and major-trace elemental geochemistry of six garnet grains from the representative Tiemurt Cu-Pb-Zn-(Au) deposit. Two categories of garnets, Grt1 and Grt2, are identified with distinct mineral assemblages, textures and chemistry. The sub- to euhedrual, mineral inclusion-rich Grt1 with fined-grains of less than 0.3 cm in diameter is intergrown with amphibole, chlorite and biotite. Comparatively, the euhedrual, mineral-poor Grt2 with coarser-grains of 0.5-5 cm in diameter is paragenetic with quartz, calcite, chlorite and biotite. Forty-one EMPA analyses show that both Grt1 and Grt2 have the similar major elemental compositions of SiO2 (36.2-37.5 wt.%), Al2O3 (19.9-20.7 wt.%) and CaO (5.3-7.8 wt.%), but host different contents of FeO (31.7-35.9 wt.% for Grt1, 23.0-30.0 wt.% for Grt2) and MnO (0.8-3.7 wt.% for Grt1, 4.3-12.7 wt.% for Grt2). Nevertheless, both Grt1 and Grt2 are plotted into the field close to almandine (Fe-Al-garnet) endmember. Compared to Grt1, Grt2 displays a Fe-enriched, Mn-depleted trend. Additionaly, Manganese (Mn) is enriched in core but Fe is enriched in rim on the major elemental profile of Grt1. In combination with the spike diagram of trace elements and REE, Grt2 is believed to be produced during the detriment and replacement of Grt1 by an intense external metal-rich fluid. As revealed by previous fluid inclusions research, the fluids characterize CO2-rich, methosthermal, mildly acidic and reduced redox, analogous to metamorphic fluids generated by orogenesis. Collectively, we conclude that the reddish gem-grade garnet crystals in Chinese Altay Orogen are metamorphic origin.